A centralized student information system for information and communications technology center of Ateneo de Naga University - Rojano, Froilan B. (Animo Repository, 2004)
The Centralized Student Information is designed for the use of Information and Communications Technology Center of Ateneo de Naga University. It aims to provide the ICTC with a centralized system to relieve the staff of routinely tasks and increasing paper works brought by manual business processes. It also aims to provide administrators easy access to pertinent information. The system integrates the major functions of the ICTC such as student record management, enrollment, student advisement, and report generation.